Validação e aplicação do bioensaio DR CALUX® para triagem de contaminação por dioxinas, furanos e bifenilas policloradas em gordura de aves - Gracielle Rodrigues Pereira (2019)
The DR CALUX® method was validated for the analysis of dioxins, furans and dioxin-like polychlorinated biphenyls in poultry fat aiming its application in the samples screening of the national program of the Ministry of Agriculture, Livestock and Food Supply (MAPA). 20 replicates of naturally contaminated samples, at three concentration levels, and the blank sample were analyzed in four different runs, under repeatibility and intermediate precision conditions. The validate range covered the critical levels for the screening, e.g., the maximum limit and the cut-off limit. The selectivity rate was 90% meanwhile the sensitivity rate were between 95 and 100%. The false results rates were low, as the value obtained for false-positives was 10% and for false-negatives were between 0% and 5%. The unreliability region (UR) was estimated between -0,20 (so, not different from zero) and 0,94 pg TEQ-WHO/g of fat, based on 5 and 95% of positive results, respectively, being the detection limit defined as the upper limit of this region (0,94). Method precision was demonstrated with accordance and concordance values of 1,00 out of the UR. 36 routine samples were analyzed and the results were compared with those obtained by the confirmatory method. These results, associated with an evaluation of the historical of samples analyzed for this scope, by the national program, indicated the DR CALUX® applicability as a screening strategy, simplifying and promoting a higher sample throughput to the monitoring process of the referred contaminants in the Brazilian food chain